NUT carcinoma of the mandible in a child: case report and systematic review. Issue 3 (March 2023) - Jimenez, C.; Stanton, E.; Kondra, K.; Nickels, E.M.; Jacob, L.; Shah, R.; Hammoudeh, J.A.
Abstract: Nuclear protein of the testis (NUT) carcinoma is a rare, undifferentiated carcinoma that is characterized by NUTM1 gene rearrangements. Patients with NUT carcinoma have an overall survival of approximately 5% at 5 years despite a multimodal treatment approach. This report illustrates the management of mandibular NUT carcinoma in a pediatric patient, complemented by a systematic review of head and neck NUT carcinoma. A 5-year-old female presented with an enlarging jaw mass that was diagnosed as BRD4-NUTM1 carcinoma and was treated with hemimandibulectomy and chemoradiation. She remains disease-free 21 months after completion of therapy. A total of 63 patient cases reported in 34 articles were identified in the review. Only 26.9% (14/52) of tumors were correctly diagnosed initially as NUT carcinoma, whereas 73.1% (38/52) were incorrectly diagnosed as another malignancy; the initial diagnosis was not reported for 11 patients. The mandibular tumor subtype was among the rarest reported ( n  = 1; 1.6%). Combination therapy, including surgery and chemoradiation, was the most common treatment (55.2%). The patient case presented here is a novel case of pediatric mandibular NUT carcinoma. Due to the poor overall survival of patients with NUT carcinoma, aggressive upfront resection with 2-cm margins followed by adjuvant chemoradiation is advocated.